Comorbidities associated with the severity of COVID-19, and differences across ethnic groups: a UK Biobank cohort study - Rahul Patel; Jaspal S. Kooner; Weihua Zhang (BMC, 2023)
Abstract Background Disparities in COVID-19 outcomes exist on the basis of ethnicity and comorbidities. Minority ethnic groups in the UK are known to have poorer COVID-19 outcomes, but also an increased prevelance of certain comorbidities associated with severe outcomes. Additionally, despite the prevalence of certain psychiatric disorders there is a lack of research establishing their relationship with COVID-19 outcomes. Methods We used UK Biobank data, involving 472,182 participants, to test for an association between comorbidities and COVID-19 diagnosis (n = 30,901); and to test for an association between comorbidities and severe COVID-19 (n = 3182). This was done by performing univariable and multivariable logistic regression analysis, estimating odds ratios (ORs) and their 95% confidence intervals (95% CIs). The comorbidities studied were coronary heart disease (CHD), hypertension, type II diabetes mellitus (T2DM), obesity, chronic kidney disease (CKD), depression and anxiety. Multivariable models were adjusted for various socioeconomic, demographic and health-related confounders. We then performed sub-group analysis by common UK ethnic groups (White, South Asian, and Black). Results Increased prevalence of all studied comorbidities was seen in both outcomes, compared to the rest of the cohort. All studied comorbidities were associated with an increased risk of COVID-19 infection and severity across all models. For example, the adjusted ORs (95% CI) for depression were 1.112 (1.083 - 1.161) for COVID-19 diagnosis and 2.398 (2.163 - 2.658) for severe COVID-19. Sub-group analysis revealed stronger associations of COVID-19 diagnosis and severe COVID-19 for South-Asian participants for CHD (OR 1.585 [95% CI 1.194-2.105] for COVID-19 diagnosis and 3.021 [1.683-5.390] for severe COVID-19), hypertension (1.488 [1.231-1.799]; 3.399 [1.862-6.206]) and T2DM (1.671 [1.346-2.076]; 5.412 [3.130-9.357]) compared to White participants (1.264 [1.195-1.336] and 1.627 [1.441-1.837] for CHD; 1.131 [1.097-1.116] and 2.075 [1.885-2.284] for hypertension; 1.402 [1.331-1.476] and 2.890 [2.596-3.216] for T2DM). Similar results were seen for Black participants with CKD and hypertension. Conclusion Specific comorbidities are risk factors for poorer COVID-19 outcomes, supporting targeted interventions and policy aimed at individuals with these comorbidities. Although further research is required, there's also a need for targeted policies for ethnic minorities assessing the unique reasons they are at greater risk of poor COVID-19 outcomes.